Flexible graphene paper electrode prepared via polyvinyl alcohol-assisted shear-exfoliation for all-solid-state polymer supercapacitor application. (10th December 2020) - Khanam, Zeba; Liu, Jianghe; Song, Shenhua
Abstract: Herein, an environmentally-benign, facile, efficient, low-cost, scalable fabrication process of achieving flexible graphene paper electrode at ambient conditions is reported. By means of high-shear exfoliation of graphite in aqueous polyvinyl alcohol (PVA), the graphene/PVA dispersion is prepared. Various characterizations (transmission electron microscopy, scanning electron microscopy, Raman spectroscopy, etc.) confirm that the resulting dispersion is with the presence of high-quality, single to few-layered graphene sheets with thickness up to 1.68 nm, lateral size of 0.5–2 μm, and low defect density ( I D / I G = 0.09). Further, the applicability of the in-situ exfoliated graphene/PVA dispersion is demonstrated for the fabrication of flexible conductive paper electrodes through a simple intermittent soaking-drying approach. The graphene paper electrode possesses an electrical sheet resistance of 15 Ω sq −1, without any additional annealing treatment and conductive additives. Finally, the graphene paper electrode is integrated with ionic-liquid incorporated PVA polymer electrolyte to develop the all-solid-state supercapacitor. It imparts a considerable specific capacitance of 222.96 F g −1 along with 60% capacitance retention and 100% coulombic efficiency after 6000 charge–discharge cycles. Meanwhile, the polymer electrolyte exhibits a remarkable ionic conductivity (4.63 × 10 −4 S cm −1 ) together with a wide electrochemical stability window (5.1 V), favorable for device applications. The unique interwoven nanoporous conductive network of PVA-stabilized exfoliated graphene provides fast diffusion pathways to electrolyte ions, thus significantly enhancing the charge-storage performance. Graphical abstract: Image, graphical abstract